Socio-demographic and clinical determinants of self-care in adults with type 2 diabetes: a multicenter cross-sectional study in Zhejiang province, China - Xuefen Lan; Xiaozhen Ji; Xiaojia Zheng; Xiaoyu Ding; Hongyi Mou; Shunfei Lu; Bin Ye (BMC Public Health)
Abstract Background Self-care, a process of maintaining health through health-promoting practices and managing illness, is pivotal for the management of type 2 diabetes. This study aimed to explore the self-care level and investigate its socio-demographic and clinical determinants among Chinese adults with type 2 diabetes. Methods In this multicenter cross-sectional study, we enrolled 495 Chinese adults with type 2 diabetes from the outpatient departments of three tertiary hospitals in Zhejiang province, China. The Self-Care of Diabetes Inventory (SCODI) was used to measure self-care maintenance, self-care monitoring, and self-care management as three critical components of the dynamic self-care process. Self-care self-efficacy is a critical factor affecting the self-care process, which was measured by the SCODI. Multiple quantile regression models were employed to identify the determinants of each self-care component and self-care self-efficacy. Results Participants had a median age of 62 years, of whom 55.4% were male. The median scores for self-care maintenance, self-care monitoring, and self-care management were 66.67 (50.00-85.42), 47.06 (32.35–58.82), and 53.13 (34.38–68.75), respectively, whereas the median score for self-care self-efficacy was 70.45 (52.27–84.09). Living in the southwest of Zhejiang province and having lower self-care self-efficacy were associated with lower self-care maintenance. Female gender, belonging to minorities, having complications, not attending diabetes self-management education in the last year, living in the southwest of Zhejiang province, and having lower self-care self-efficacy were associated with lower self-care monitoring. Having complications, using insulin, living in the southwest of Zhejiang province, and having lower self-care self-efficacy were associated with a lower level of self-care management. Living in the southwest of Zhejiang province was associated with lower self-care self-efficacy. Conclusions/interpretation The findings of this study provide invaluable insights into the factors affecting self-care among Chinese adults with type 2 diabetes. By enhancing self-care self-efficacy and participating in diabetes self-management education, healthcare providers can develop tailored self-care interventions to improve diabetes care, particularly for adults with type 2 diabetes who are female, belong to minority groups, have complications, use insulin, or reside in the southwest of Zhejiang province.